On the Liouville and strong Liouville properties for a class of non-local operators - Berger, David; Schilling, René L. (MATHEMATICA SCANDINAVICA, 2022)
We prove a necessary and sufficient condition for the Liouville and strong Liouville properties of the infinitesimal generator of a Lévy process and subordinate Lévy processes. Combining our criterion with the necessary and sufficient condition obtained by Alibaud et al., we obtain a characterization of (orthogonal subgroup of) the set of zeros of the characteristic exponent of the Lévy process.